Analysis and Improvement of Product Defects Using the Fishbone Diagram Method (Case Study: 100 Gram Skincare Packaging) - Shanti Kumbarasari; Bagus Agung Nugrahanto; Bina Ikhwan Mubarok (Magister Teknik Mesin Universitas Pancasila, 2026)
This study aims to reduce the flash defect rate in the injection molding process of 100-gram skincare packaging products. The initial analysis showed that out of a total production of 125,231 units, flash defects reached 480 units or 0.38%, making it the most dominant type of defect. The main cause of this defect was identified as damage to the bushing sleeve and sleeve mold components. Based on the analysis using the Fishbone Diagram method, the flash defect was caused by nonconforming air venting exceeding the 0.02 mm standard, gate imbalance, miscalculation of the required clamping force, and wear of the bushing sleeve and sleeve components due to improper material selection. Improvement efforts were carried out through the implementation of preventive maintenance, mold design improvements, and the replacement of the sleeve material from Rapidur 3343 to S705 tool steel. The implementation results show a significant reduction in flash defects, from 480 units to 83 units in July with a total production of 143,813 units, equivalent to 0.06%. This study proves that the application of the Fishbone Diagram method combined with material improvement and mold maintenance is effective in improving product quality and the productivity of the injection molding process. Consequently, product quality can be enhanced, and the company’s competitiveness in the market can be strengthened